Potrzeba harmonizacji ubezpieczeniowych programów gwarancji w Unii Europejskiej - Janusz, Alicja (The Necessity of Insurance Guarantee Programs Harmonization in the European Union, 2005)
The objective of the hereby article is to answer the question whether an ongoing legal regulations’ harmonization process, with regard to the European insurance market, should also refer to the insurance guarantee programs. In order to carry out such a defined objective the analysis of how the lack of national regulations’ harmonization, with regard to insurance guarantee programs, influences the situation of the insurance services’ consumer in the European Union countries was presented. Prior to the analysis the presentation of the nature of insurance guarantee programs and the forms in which they may be carried out was provided, as well as their influence on the insurance facilities market was included. Additionally the article presents conclusions resulting from the hitherto practice of EU membership countries in the discussed field.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1091, s. 145-155